Value Chain and Supply Chain Management of Products from Women Farmer Groups in South Tangerang - Tukhas Shilul Imaroh; Katri Widiyani; Fauzan Muttaqien (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
This study aims to analyze the operational process of the production of Farmer Women's groups effectively based on supply chain management, and determine the internal condition of the organization by using value added analysis (value chain). The analytical method used is supply chain management and value chain analysis. The purpose of this research was to find out and analyze the Supply Chain Management and value chain analysis of products produced by the Farmer Women's Group. The data analysis method used in the framework of assessing the performance of internal value added with Value Chain Analysis and knowing the process of the supply chain or supply chain. This research is included in TKT 2, namely formulating the concept of technology and its application to the UKM object of the Cempaka Farmers' Group in South Tangerang. The results obtained were three superior products, namely cumin plants and their preparations, python plants and their preparations, and butterfly pea plants and their preparations. Value chain by formulating the main factors and supporting factors for activities that must be carried out by KWT Cempaka.